Karakteristik jerapan fosfat ‘kleinano’ terseparasi dari tuf volkan Indonesia - Untung Sudadi; Muhammad Anggi Imaduddin; Iskandar Iskandar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
From an Indonesian volcanic tuff taken from parent material layer of an Andisols profile, it was separated ‘nanoclay’ fraction of <200 nm particle size. The separated ‘nanoclay’ exhibits pH-dependent charge characteristic due to the presence of allophane in the tuff. Therefore, it can be utilized as a natural anionic adsorbent since its separation process was conditioned to proceed at pH <4.0. This study aims to compare phosphate adsorption characteristics of positively charged ‘nanoclay’ based on Langmuir, Freundlich, Brunauer-Emmett-Teller (BET), and Dubinin-Radushkevich (D‒R) isothermal models. The ‘nanoclay’ was separated using US Patent No. US2010/0187474 A1 procedure that was modified in this study with addition of HCl treatment. The results showed that after 48 h equilibration, application of Langmuir and D‒R model resulted adsorption capacity (qe para-meter) of 460.78 (two-sites) and 439.66 mg.g-1 (heterogeneous sites), respectively, while BET and Freundlich model resulted respectively adsorption at the first adsorptive layer (qmono parameter) of 111.11 mg.g-1 (multilayers) and adsorption constant (1/n parameter) of 0.28. The later indicated that the studied ‘nanoclay’ was a high-quality adsorbent (1/n value 0.1-0.5). Limitations and advantages application of each model were discussed. However, Langmuir showed the best performance in term of linear equations with the highest R2 values obtained.